Peran Audit Internal dan Komite Audit Atas Tercapainya Penerapan Good Corporate Governance Pada PT. PP. London Sumatera Indonesia Tbk. Divisi Gunung Melayu Estate - Teguh Fahmi; Kamilah Kamilah; Khairina Tambunan (LPPM Universitas Labuhanbatu, 2023)
the purpose of this study is to determine the role of internal audit and audit Committee on the achievement of the implementation of good corporate governance at PT. PP London Sumatera Indonesia Tbk. Malay Mountain Division Estate. This research method uses qualitative research approach with descriptive approach. Information or data obtained through the results of interviews with the parties concerned and based on the annual report in 2021, then the data is classified according to the problems discussed. The findings of this study that the internal audit and the audit committee plays a role in the achievement of Good Corporate Governance by controlling the internal audit function to help ensure that the risk management process, the overall scope of control and the effectiveness of performance, the internal audit function is currently not only required to find problems, but also become part of the solution and provide suggestions for improvement. Internal Audit is involved and plays an active role in monitoring the activities of operational units and providing a consultative role in the implementation of the company's operating processes. Thus, the role of internal audit is not only limited to detectors, but can be more as a deterrent that is expected to be able to encourage and create Good Corporate Governance.